(untitled) (Konferensiyalar | Conferences, 2023)
This article examines the definition of news and news text in journalism and medialinguistics, where it is usually stated as the object of research. To achieve the aim of the article, comparison, analysis, and synthesis methods have been used. Findings demonstrate that research in journalism mostly covers the topic of news value and defines news as information that has novelty. Whereas medialinguistics describes the format, specific sentence structure, and linguistic units of news. Combining these definitions, it was concluded that the definition given by journalists helps to choose what could be defined as news; in contrast, medialinguistics studies the representation, format, and other linguistic features of that news. The results of this article give a more comprehensive understanding of the nature of news texts.